The putative tumor suppressor VILIP-1 counteracts epidermal growth factor-induced epidermal-mesenchymal transition in squamous carcinoma cells. - Katharina Schönrath; Andres J Klein-Szanto; Karl H Braunewell (PLoS ONE, 2012)
Epithelial-mesenchymal transition (EMT) is a crucial step for the acquisition of invasive properties of carcinoma cells during tumor progression. Epidermal growth factor (EGF)-treatment of squamous cell carcinoma (SCC) cells provokes changes in the expression of lineage markers, morphological changes, and a higher invasive and metastatic potential. Here we show that chronic stimulation with EGF induces EMT in skin-derived SCC cell lines along with the down-regulation of the epithelial marker E-cadherin, and of the putative tumor suppressor VILIP-1 (visinin-like protein 1). In esophageal squamous cell carcinoma and non-small cell lung carcinoma the loss of VILIP-1 correlates with clinicopathological features related to enhanced invasiveness. VILIP-1 has previously been shown to suppress tumor cell invasion via enhancing cAMP-signaling in a murine SCC model. In mouse skin SCC cell lines the VILIP-1-negative tumor cells have low cAMP levels, whereas VILIP-1-positive SCCs possess high cAMP levels, but low invasive properties. We show that in VILIP-1-negative SCCs, Snail1, a transcriptional repressor involved in EMT, is up-regulated. Snail1 expression is reduced by ectopic VILIP-1-expression in VILIP-1-negative SCC cells, and application of the general adenylyl cyclase inhibitor 2',3'-dideoxyadenosine attenuated this effect. Conversely, EGF-stimulation of VILIP-1-positive SCC cells leads to the down-regulation of VILIP-1 and the induction of Snail1 expression. The induction of Snail is inhibited by elevated cAMP levels. The role of cAMP in EMT was further highlighted by its suppressive effect on the EGF-induced enhancement of migration in VILIP-1-positive SCC cells. These findings indicate that VILIP-1 is involved in EMT of SCC by regulating the transcription factor Snail1 in a cAMP-dependent manner.